2007
DOI: 10.1016/j.abb.2007.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Zinc as an anti-tumor agent in prostate cancer and in other cancers

Abstract: Human prostate glandular epithelial cells have the unique capability of accumulating high levels of zinc. This is essential to inhibit m-aconitase activity so that citrate can accumulate for secretion into prostatic fluid, which is a major function of the prostate gland. As a result, the Krebs cycle is truncated with the consequence of the lost ATP production that would result from citrate oxidation. The cellular accumulation of zinc also inhibits mitochondrial terminal oxidation and respiration. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 62 publications
4
142
1
4
Order By: Relevance
“…zinc levels three to 10-fold higher than in other soft tissues [120][121][122]). As a consequence, citrate accumulates and is excreted into the prostatic fluid.…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 85%
See 1 more Smart Citation
“…zinc levels three to 10-fold higher than in other soft tissues [120][121][122]). As a consequence, citrate accumulates and is excreted into the prostatic fluid.…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 85%
“…As a consequence, citrate accumulates and is excreted into the prostatic fluid. In an early step during the transition from healthy to malignant tissue, prostate cells lose their ability to accumulate zinc due to the downregulation of zinc transporters (mainly ZIP1) [122,123]. Therefore, the block of the tricarboxylic acid cycle is relieved and the cells switch their metabolism to generate energy via oxidation of citrate and coupled respiration.…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 99%
“…Since the early Mawson 16 innumerable studies consistently demonstrated that zinc levels and citrate levels are markedly decreased (~60-90%) in prostate cancer as compared with normal and benign prostate. [1][2][3][4] For example normal prostate peripheral zone (where most malignancies arise and develop) contains approximately 3,000 nmols zinc/gm tissue, as compared with 600 nmols/gm in cancer. The citrate levels are approximately 13,000 and 1,000 for normal vs. cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that zinc and citrate levels are virtually always markedly decreased in prostate cancer as compared with normal and benign prostate (for reviews see ref. [1][2][3][4]. This relationship currently, in our view, is the most consistent and persistent "hallmark" characteristic of human prostate cancer, which distinguishes prostate cancer from normal and benign prostate.…”
Section: Introductionmentioning
confidence: 98%
“…[2][3][4] In such cancers, the zinc levels of malignant tissue are markedly decreased as compared with the normal tissue. At this pancreatic adenocarcinoma is an untreatable deadly cancer.…”
Section: Introductionmentioning
confidence: 99%